2000
DOI: 10.1007/pl00010342
|View full text |Cite
|
Sign up to set email alerts
|

A Scenario Construction Process

Abstract: Scenario is a description

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(34 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Different techniques have been proposed in literature for eliciting requirements from stakeholders [11,16,25,62]: interviews, questionnaires, user observation, workshops, brain storming, use cases and prototyping. Our approach in TAS 3 is mainly based on interviews and use cases.…”
Section: Requirements Elicitationmentioning
confidence: 99%
“…Different techniques have been proposed in literature for eliciting requirements from stakeholders [11,16,25,62]: interviews, questionnaires, user observation, workshops, brain storming, use cases and prototyping. Our approach in TAS 3 is mainly based on interviews and use cases.…”
Section: Requirements Elicitationmentioning
confidence: 99%
“…Figure 10 shows the statistics for the use case templates where we found that no such evidences about their practical implications (i.e., no study falls under Evaluation Research Category). The five use case templates namely Insfrán et al [71], Somé [131], Leite et al [39], Yue et al [151] and El-Attar et al [47] were evaluated by conducting some small experiments/case studies; six use case templates namely, Liu et al [98], Mushabiddin et al [102], Fleisch [52], Tiwari et al [141], Toro et al [143], and Mattingly et al [99] were proposed to provide the solutions to the problem, and rests were based on the experiences of the researchers gained from the industries or academia. Among all, two [86,64] use case templates were commonly used in the industrial context, but their practical implications, i.e., understandability, learnability and operability aspects are not evaluated.…”
Section: Which Use Case Template Information and Style Is Most Usefulmentioning
confidence: 99%
“…With reference to a purely informative perspective the use case specification were documented in a tabular or a paragraph style format with minimal degree of formalism (e.g., [32,39,64,74,86,143] etc). The rationale behind this was to elicit, analyze and validate the problem specifications with the viewpoint of stakeholders and developers.…”
Section: Research Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…This comes besides with no guarantee on the quality of the requirements. To improve the quality of the requirements, one can consider scenarios with important advantages already addressed in the literature [2,3]. For instance, scenarios tend to adopt the user's viewpoint, which is a key feature to validate the adequacy between the requirements and the user's needs.…”
Section: Introductionmentioning
confidence: 99%